Importance of Medhya Rasayana Drugs Used in the Treatment of Mental Stress. - Patel, Shambhu P; Kumar, Sunil; kumar, Sujit; Aggarwal, Sandeep (International Research Journal of Ayurveda & Yoga, 2021)
Medhya Rasayana is an Ayurvedic nootropic herb or drug that improves memory and cognitive functions. Ayurvedic nutrients such as Medhya Rasayana help with memory, retention and recall. Medhya Rasayan is made up of Mandukparni (Centella asiatica), Guduchi (Tinospora cordifolia), Yasthimadhu (Glycyrrhiza glabra) and Sankhpushpi (Convolvulus pluricaulis), as defined by Acharya Charaka in Chikitsasthan 1:3/30. Stress is a social condition that affects nearly everyone at some stage in their lives. It is caused by being under so much mental or emotional strain. Stress is not a disease in and of itself, but it can lead to severe illness if left untreated, so it’s crucial to consider stress symptoms early on. Ayurveda has a long history of stress control. One of the most effective Ayurvedic formulations or supplements is "Charaks Medhya Rasayana," which enhances intellect, memory, knowledge, imagination, learning abilities and executive functions among other things. Furthermore, these vitamins enhance immune system functions and increase immunity. These herbs have the ability to have these effects on the human brain because of their inherent properties. Furthermore, we should take simple steps to alleviate discomfort, such as improving our lifestyle and doing yoga.